Cryoneurolysis and Quadriplegia: A Case Report on Pain and Severe Spasticity Management - Laura Schatz, BSc; Samuel Herzog; Mahdis Hashemi, MD; Paul Winston, MD (Archives of Rehabilitation Research and Clinical Translation)
Spasticity, a common symptom after spinal cord injury, often leads to pain, muscle contracture, and compromised daily activities. Cryoneurolysis, a minimally invasive, drug-free procedure for the treatment of pain, is now gaining recognition for treating spasticity. It involves using an ultrasound-guided probe to freeze and destroy overactive target nerves. The objective of this case study was to assess the effect of cryoneurolysis on joint range of motion (ROM) by reducing spasticity and pain in a person with quadriparesis spinal cord injury. A 52-year-old male with C4 incomplete quadriplegia presented with severe right hip osteoarthritis, causing a severe hip flexion deformity with hip flexor spasms, as well as spasticity in the upper limbs. Previous attempts with exceeding maximum-dose botulinum toxin injections for the lower limb proved insufficient to improve ROM. Percutaneous cryoneurolysis was performed on multiple nerves, contributing to spasticity in the upper and lower limbs. Immediately after each procedure, the patient experienced an increased ROM in the upper and lower limb targeted regions. During the patient's follow-up, he also reported improvements in performing daily activities, such as independent showering, no falls, and a significant decrease in muscle tone. Results were primarily maintained up to 9 months postprocedure when cryoneurolysis was repeated for the lower limbs only. On repeat cryoneurolysis, results were re-established. Cryoneurolysis is a nonsurgical, percutaneous procedure that could be considered for pain and spasticity management in patients with quadriplegia. It can provide an option for improved quality of life and independence for patients.